A Laboratory Assessment of Two Local Strains of the Beauveria bassiana (Bals.) Vuill. against the Tetranychus urticae (Acari: Tetranychidae) and Their Potential as a Mycopesticide. (8th November 2017) - Ortucu, Serkan; Algur, Omer Faruk
Abstract : This study was conducted to assess highly pathogenic Beauveria bassiana isolates to be used in biocontrol and to determine their potentials as mycopesticide. For this purpose, two B. bassiana isolates, which were locally isolated from T. urticae, were chosen. Firstly, three suspensions were investigated at the degree of humidity of 65 ± 5% and 100% RH. Secondly, these strains were selected according to their tendency to mass production, tolerance to UV radiation, and capability of producing spore at the different temperatures. Finally, identification of the selected isolate was performed by using ITS rDNA analysis. Both tested fungal isolates were pathogenic to the T. urticae . Mycelial growths of isolate AT076 at 20°C and 30°C were found to be greater than isolate AT007. It was observed that isolate AT076 had more spore production with 1.61 × 10 7 spore/disc at 30°C and 44.33% germination after UV radiation for 15 min. The numbers of spores per 5 mm disk area for isolates AT076 and AT007 were found to be 1.2 × 10 6 and 1.0 × 10 6 . These results show that isolate AT076 was more virulent and more UV-tolerant and had higher tendency to mass production compared to isolate AT007 against T. urticae . As a result of this study, isolate AT076 can be used in the biocontrol as mycopesticide.